Tarekat in the Digital Age: Transforming Spirituality for the Age of Technology - Hasibuan, Armyn; Nasution, Ismail Fahmi Arrauf; Masuwd, Mowafg (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2024)
This article explores the influence of the digital era on spiritual practices within the context of Tarekat Sufism. Using a qualitative approach incorporating in-depth interviews, participatory observation, and content analysis of digital Sufism platforms, this study examines the changes in rituals, the evolving role of spiritual teachers, and the integration of digital technology in spiritual life. Tarekat, shaped by the experiential knowledge of Sufi masters, intersects with digital advancements enabling seamless access to a vast array of resources in cyberspace. The findings reveal that digital technology has significantly impacted spiritual practices within Tarekat Sufism. These include easier access to spiritual guidance through online platforms, the proliferation of Sufism applications and digital content, and the formation of online communities fostering spiritual connection. However, the challenges such as the risk of spiritual commodification, the reduced personal interaction with spiritual teachers, and the maintainance of authenticity in digital spiritual practices are also observed. This research contributes to the academic discourse by highlighting the intersection of spirituality and technology, offering a nuanced understanding of how digital tools reshape traditional Sufi practices. Methodologically, it underscores the utility of combining qualitative methods with digital ethnography to study the evolving spiritual phenomena. These insights provide a foundation for further exploration of the balance between tradition and innovation in the context of digital spirituality.